DNFB activates MAPKs and upregulates CD40 in skin-derived dendritic cells - Matos, TJ (2010)
BACKGROUND: The intracellular mechanisms involved in the activation of DCs during sensitization in allergic contact dermatitis (ACD) are not known. OBJECTIVE: Here, we investigated the effect of a strong sensitizer, 2,4-dinitrofluorobenzene (DNFB) on the activity of MAPKs in a dendritic cell (DC) line generated from fetal mouse skin (FSDC), and the results were correlated with the expression of a costimulatory molecule upregulated upon DC maturation, CD40. METHODS: Phosphorylation of ERK1/2 (pERK1/2) and p38 MAPK (pp38 MAPK), and CD40 protein levels, were determined by Western blot. Cellular localization of pERK1/2 and pp38 MAPK were determined by immunocytochemistry using phospho-specific antibodies. RESULTS: Although with different kinetics, DNFB activated ERK1/2 and p38 MAPK, and induced the translocation of the phosphorylated forms of the kinases to the nucleus. In addition, DNFB upregulated significantly CD40 protein levels in FSDC. However, 2,4-dichloronitrobenzene (DCNB), an inactive analogue of DNFB, did not affect significantly the phosphorylation of MAPKs and CD40 protein levels. SB203580 and SB202190, inhibitors of the p38 MAPK activity, inhibited DNFB-induced CD40 upregulation, although this effect did not reach statistical significance. In contrast, PD 98059 and U0126, inhibitors of mitogen or extracellular signal-regulated kinase (MEK), had no effect on the CD40 upregulation induced by DNFB. CONCLUSIONS: Taken together, these results indicate that the strong sensitizer DNFB activates ERK1/2 and p38 MAPK signaling pathways, and upregulates CD40 protein levels. However, MAPKs do not play a major role in the induction of CD40, one of the phenotypic markers of DC maturation.